Religious Responses to Globalisation - Kadir, Hatib A.; Maufur, M. (Al-Jamiah Research Centre, 2011)
Sociological discussion of globalisation is preoccupied with the political, economic, and military dimension of it, with little attention to its religious aspect. This paper attempts to trace the impacts of globalisation on religion and religious responses, the argument of which derives mainly from the so-called âBridge-Building Programâ organised by CRCS & ICRS-UGM in 2008. It argues that though they share a common concern, people of different faiths are at risk of deepening the problems rather than offering solutions in view of their different responses for which we categorise them into different but overlapping categories -ideological, ambivalent, integrative, exclusive, and imitative. It then leads to a more fundamental question of whether interfaith cooperation is possible given those different and sometime opposing responses.[Dalam kajian sosiologi, diskusi mengenai globalisasi kerap kali semata-mata ditinjau dari sisi politik, enonomi dan militer, sementara dimensi agama sering kali dikesampingkan. Artikel ini membahas dampak globalisasi terhadap agama dan respon komunitas agama terhadap globalisasi. Data yang muncul dalam artikel ini diambil dari sebuah workshop berjudulâBridge- Building Program.â Melalui artikel ini, saya berpendapat bahwa, meskikomunitas agama-agama memiliki keprihatinan yang sama terhadap dampak globalisasi, namun respon mereka cenderung mempertajam persoalan yang diakibatkan globalisasi, ketimbang memberikan solusi. Respon tersebut dalam dikategorikan âmeski tidak kaku- dalam: respon ideologis, ambivalen, integratif, ekslusif dan imitatif. Selanjutnya, artikel juga mengulas pada pertanyaan mendasar mengenai apakah kerjasama antar agama mungkin dilakukan menyimak ragam respon yang saling bertentangan tersebut.]